Insecticide-releasing LLDPE films as greenhouse cover materials - Seven, Senem Avaz; Tastan, Omer Faruk; Tas, Cuneyt Erdinc; Unal, Hayriye; Ince, Ikbal Agah; Menceloglu, Yusuf Ziya (ELSEVIER, 2019)
The use of chemical pesticides is limited by several public health concerns regarding their toxicity levels and indiscriminate use. Nevertheless, they are still vital components of agricultural industry since no other competitive equivalents to chemical pesticides still exist in terms of efficiency. This study describes the preparation and biological assessment of an insecticide releasing plastic film for agricultural covering purposes. The formulation was prepared by incorporation of deltamethrin loaded, nano-sized halloysite nanotubes into polymeric films. Thermal, morphological, and mechanical properties of films were characterized by Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM) and Universal Testing Machine UTM. Sustained release profiles of the films were evaluated by Thermogravimetric Analysis (TGA). Results reveal that deltamethrin was successfully loaded into halloysite nanotubes and nanotube incorporation enhances the elastic modulus of linear-low density polyethylene (LLDPE) films. In addition, films exhibit sustained release function of the active agent for 60 days. Bioassays of the nanocomposite films with varying deltamethrin doses tested on grasshoppers showed that the LD(50 )values of the films are 1.85x10(-5) g/cm(2). Insecticidal activities of films were tested in greenhouse on Medicago Saliva plants contaminated with thrips and aphid. Nanocomposites are observed to repel mature aphids and kill young aphids and thrips.
Keywords: Halloysite nanotubes; Insecticide; Sustained release; Sustainable agriculture